Implementasi Pendidikan Non Kurikulum Dalam Pembentukan Akhlak Di Mts Muhammadiyah 1 Gondangrejo - Anjelia Saputri, Della; Zakki Azani , Mohammad (AL MURABBI, 2023)
This research discusses about the Implementation of non-curriculum education to strengthen formal education role at MTs Muhammadiyah 1 Gondangrejo. Non-curriculum education here includes various extracurricular activities, moral formation, and development of additional skills carried out at school. The focus of this research is to understand how non-curriculum education is integrated in the context of formal and non-formal educational institutions, with an emphasis on its role and impact on student development. The method used in this research is through data collection techniques, observation and interviews, which were carried out using a qualitative phenomenological approach. The objects of this research are school principals, teachers, student guardians and students at MTs. The sources used are data from data collection and interviews. The results of this research show that the implementation of non-curriculum education in the formation of morals is with planned program strategies, such as study of climbing heaven, student of the moon, parenting every 3 months, reading and writing the Qur'an (BTA), Murottal Qur'an and Asmaul Husna Before Teaching and Learning Activities (KBM), Dhuha prayers, and Guidance During the Ceremony by Outside Figures. Apart from that, it also provides good examples regarding morals to students, and provides advice to students regarding morals.